P668 Ustekinumab induction effectiveness in Crohn's disease in a real-life cohort. (25th January 2019) - Rullan, M; Elosua, A; Saldaña, C; Amorena, E; Vicuña, M; Rubio, S; Nantes, Ó; Rodríguez, C
Abstract: Background: Ustekinumab (UST), a humanised monoclonal antibody targeting the IL-12/23 shared p40 subunit, was approved in Spain in 2017 for treatment of moderate-to-severe Crohn's disease (CD). The aim of this study was to analyse the patients' characteristics starting UST in a real-life cohort and the induction effectiveness. Methods: A retrospective observational study including patients initiating UST between August 2017 and September 2018 was conducted in a single tertiary centre. We recorded demographic and descriptive variables, activity indexes Crohn's Disease Activity Index (CDAI) and Harvey–Bradshaw (HB), inflammatory markers, and the reason to start UST. Induction effectiveness was analysed in patients who had reached Week 16. Response was defined as a reduction 100 points in CDAI and remission if CDAI was 150. A response/remission Physician's Global Assessment (PGA) was also done. A stratified analysis based on the reason for starting UST was performed. Results: We included 41 patients (36.6% women) with median disease duration until start of UST of 10.6 years (0–36). Most patients did not receive concomitant steroids (78%) or immunomodulatory drugs (73.2%). UST was the second biologic in 31.7%, the third in 46.3%, the fourth in 19.5% and the fifth in 2.4%. Previously, 100% had anti-TNF agents and 17.1% had Vedolizumab. The reason to start UST was primary failure in 12.2%, secondary failure 68.3% and intolerance/allergy to previous anti-TNF agents 19.5%. Baseline CDAI was 195 (18–351), HB 8 (1–13), C-reactive protein 9.5 (0.5–92.7 mg/l) and faecal calprotectin 403 (52- >3000 mg/kg). A total of 28 patients completed induction (Week 16). Response rates were 73.1%/71.4% and remission rates 65.4%/57.1% according to the CDAI criteria and PGA, respectively. All patients (6) starting UST due to intolerance/allergy responded (83.3% remission); of those with previous primary failure (3), 66.7% achieved remission and 33.3% failed; and of those with previous loss of response to anti-TNF agents (19), 63.2% responded (47.4% in remission). UST was used as second biologic (7) with 71.4% remission, as third biologic (14) with 71.4% response (57.1% remission) and as fourth biologic (5) with 80% remission. Conclusions: In this real-life cohort, two thirds of patients responded to UST after the induction, with different response rates according to treatment indication: 80% remission in patients who started UST due to prior intolerance/allergy, 60% of patients with previous primary failure and 60% of those with previous loss of response. We consider it convenient to present stratified results according to UST indication.